EFFECTS OF THERAPY ON THE ABILITY OF ERYTHROCYTES FLUVASTATIN AGGREGATION IN HYPERTENSIVE PATIENTS WITH DYSLIPIDEMIA - I. N. Medvedev; I. A. Skorjatina (Евразийский Кардиологический Журнал)
Aim: investigate the possible influence of fluvastatin on erythrocyte aggregation in hypertensive patients with dyslipidemia. Material and methods: under a supervision there were 32 patients by arterial high blood pressure 1-2 degrees, risk 3 (criteria of DAG3 (2008) with dyslipidemia II6 of type), middle age. A control group was made by 26 healthy people of analogical age. All patients received fluvastatin 40 mg at night on a background of enalapril 10 mg 2 times a day. The estimation of clinical and laboratory indexes was conducted at the beginning of treatment, through 4, 12 and 52 weeks of therapy. Statistical treatment of results was conducted t - Student criterion. Results: in hypertensive patients with dyslipidemia in the damage of blood lipid spectrum, lipid composition of erythrocyte membranes and activation of these lipid peroxidation observed increased aggregation. The use of fluvastatin in hypertensive patients with dyslipidemia over 52 weeks of optimized lipid composition, level of lipid peroxidation of plasma and red blood cells, without bringing these figures to the level of control. Appointment of fluvastatin persons suffering from hypertension with dyslipidemia, reduced the ability of red blood cells to aggregate, not allowing her to achieve a full normalization within a year of therapy.